2018
DOI: 10.1080/00036846.2018.1489503
|View full text |Cite
|
Sign up to set email alerts
|

The effect of financial development on economic growth: a meta-analysis

Abstract: Empirical studies on the finance-growth relationship show a wide range of estimated effects. We perform a meta-analysis on in total 551 estimates from 68 empirical studies that take private credit to GDP as a measure for financial development and distinguish between linear and logarithmic specifications. First, we find evidence of significantly positive publication bias in both the linear and loglinear specifications. This contrasts with findings in two other recent meta-studies, possibly due to a distortion i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 63 publications
1
27
0
Order By: Relevance
“…The findings of both studies supported the too much finance hypothesis. In a metaanalysis study by Bijlsma et al (2018) covering 68 empirical studies, they concluded that the impact of finance on growth is positive but decreases over time in line with the too much finance hypothesis.…”
Section: Review Of Literaturementioning
confidence: 88%
“…The findings of both studies supported the too much finance hypothesis. In a metaanalysis study by Bijlsma et al (2018) covering 68 empirical studies, they concluded that the impact of finance on growth is positive but decreases over time in line with the too much finance hypothesis.…”
Section: Review Of Literaturementioning
confidence: 88%
“…In another ground-breaking study, Rioja and Valev (2004) divide the sample countries into three groups according to their FD level and find that only in the group that has a middle level of FD does finance have a large and positive effect on output growth. In their words, 'financial development exerts a strong 1 However, another meta-analysis that was conducted by Bijlsma et al (2018) shows that there is a publication bias in the literature, namely, studies that report a positive effect of financial development on economic growth are more easily published. Therefore, 'the literature has exaggerated the size of the finance-growth effect in the past' (Bijlsma et al 2018:1).…”
Section: Two Generations Of Literaturementioning
confidence: 99%
“…The dependent variable, economic growth, is measured by real GDP per capita. This follows previous empirical studies that examine the relationship between economic growth and financial development (Bijlsma et al, 2018;King and Levine, 1993 denoted by y it , captures economic growth and adjusts for total population and inflation (Haini, 2020). Real GDP per capita is generally used to compare standards of living between countries and over time.…”
Section: Data and Variablesmentioning
confidence: 99%